2021
DOI: 10.18502/fid.v18i31.7236
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Fit of Temporary Restorations Fabricated by the Conventional Chairside Method, 3D Printing, and Milling

Abstract: Objectives: This study aimed to compare the marginal fit of temporary restorations fabricated by the conventional chairside method, 3D printing, and milling. Materials and Methods: In this in vitro, experimental study, 14 temporary restorations were conventionally fabricated over an implant abutment and analog that had been mounted in a phantom model at the site of canine tooth, using auto-polymerizing acrylic resin and putty index. In digital manufacturing, the original model was scanned, and the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In general, the majority (i.e., 8 out of 13) of the studies included in this review reported that marginal discrepancies were least with the provisional restorations fabricated by 3D printing when compared to those fabricated by CAD/CAM milling and conventional techniques [10,14,34,[37][38][39][40]44]. In two studies, the marginal discrepancy reported for 3D-printed provisional crowns was equal to that of those fabricated by CAD/CAM milling [5,25], whereas in two studies, the 3D-printed provisional crowns displayed the greatest marginal discrepancy [35,41]. Overall, most of the studies reported that marginal discrepancies were highest in provisional restorations fabricated using conventional techniques and materials [10,14,34,[36][37][38][39][40]44].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In general, the majority (i.e., 8 out of 13) of the studies included in this review reported that marginal discrepancies were least with the provisional restorations fabricated by 3D printing when compared to those fabricated by CAD/CAM milling and conventional techniques [10,14,34,[37][38][39][40]44]. In two studies, the marginal discrepancy reported for 3D-printed provisional crowns was equal to that of those fabricated by CAD/CAM milling [5,25], whereas in two studies, the 3D-printed provisional crowns displayed the greatest marginal discrepancy [35,41]. Overall, most of the studies reported that marginal discrepancies were highest in provisional restorations fabricated using conventional techniques and materials [10,14,34,[36][37][38][39][40]44].…”
Section: Discussionmentioning
confidence: 91%
“…The overall SMD was −0.82 (−1.37 to −0.28) in favor of 3D-printed methacrylate oligomers over conventional PMMA resin and was statistically significant (p < 0.05). (A) Evaluation performed on single crowns: Aldahian et al [40] reported lower marginal discrepancies, whereas Mohajeri et al [41] reported higher marginal discrepancies for methacrylate-based 3D-printed provisional resins when compared to conventional PMMA resins (Figure 5). The overall SMD was 0.14 (−1.18 to −0.80) in favor of 3D-printed methacrylate resin over CAD/CAMmilled PMMA resin and was statistically significant (p < 0.05).…”
Section: ) (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated several commercially available intraoral scanners and the marginal fit of prostheses fabricated with CAD/CAM systems (5)(6)(7)(8)(9)(10)(11)(12). However, few studies have examined the Three-Dimensional fit of crowns made with CAD/CAM systems to assess different scanner types.…”
Section: Issn:2753-9172mentioning
confidence: 99%